2018
DOI: 10.5713/ajas.17.0815
|View full text |Cite
|
Sign up to set email alerts
|

Effect of keratinase on ileal amino acid digestibility in five feedstuffs fed to growing pigs

Abstract: ObjectiveThis study was conducted to evaluate the effect of keratinase (KE) on the apparent ileal digestibility (AID) and standardized ileal digestibility (SID) of amino acids (AA) in rice bran, cottonseed meal (CSM), rapeseed meal (RSM), corn distillers dried grains with solubles (DDGS), and peanut meal (PNM).MethodsTwelve crossbred barrows (Duroc×Landrace×Yorkshire, 50.5±1.4 kg body weight [BW]) fitted with T-cannulas at the terminal ileum were allotted to a 12×6 Youden Square design with 12 diets and 6 peri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
7
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 33 publications
2
7
1
Order By: Relevance
“…To our knowledge, there have been no data on the SID of AA in lupin hulls reported previously. For rice bran, the SID of CP and AA observed in the present study was less than the values reported by Casas et al [15], but greater than the values by Huang et al [30]. There were variations in the CP and AA contents in the full fat rice bran used among the experiments, but the SID values are not be affected by the total contents of CP and AA [5].…”
Section: Discussioncontrasting
confidence: 74%
See 1 more Smart Citation
“…To our knowledge, there have been no data on the SID of AA in lupin hulls reported previously. For rice bran, the SID of CP and AA observed in the present study was less than the values reported by Casas et al [15], but greater than the values by Huang et al [30]. There were variations in the CP and AA contents in the full fat rice bran used among the experiments, but the SID values are not be affected by the total contents of CP and AA [5].…”
Section: Discussioncontrasting
confidence: 74%
“…The difference in fiber contents may also affect the AA digestibility in rice bran. It is possible that dietary NDF can decrease the digestibility of CP [33], and the NDF contents in rice bran were 21.4% DM in the present study (Table 1) whereas the NDF in rice bran was 23.8% DM [30] and 5.1% DM [15], respectively. The SID in wheat bran used in this study was in agreement with the values reported by Eklund et al [25].…”
mentioning
confidence: 51%
“…The performance of broiler chickens on this feed was better than with conventional soybean meal protein ( Larasati et al, 2017 ). Similarly, addition of “Versazyme” (a keratinase feed additive produced by B. licheniformis PWD-1) or other keratinases to feed mixtures may improve growth performance, breast meat yield, and gut villus structure of broilers fed diets based on corn and soybean meal ( Huang et al, 2018 ; Wang et al, 2008 , Wang et al, 2006 ). Chicken feather hydrolysates could also serve as a cheap source of liquid organic fertilizer.…”
Section: Applications Of Keratinolytic Enzymesmentioning
confidence: 99%
“…Also, the incidence of diarrhea, one of the causes of weaned piglets death was positively reduced (Wang et al 2011). Huang et al (2018) also demonstrated with pigs that the supplementation of different diets (rice bran, corn dried grains and cottonseed, rapeseed, peanut and corn-soybean meals) with Cibenza DP100™ keratinase at 0.05% (w/w), affected crude protein and most of the analyzed amino acids to apparent and standardized ileal digestibility (AID and SID, respectively). The highest AID and SID for most amino acids were observed for corn-soybean and peanut meals whereas rice bran and corn dried Biogas production (hydrogen) Bálint et al (2005) grains diets presented the lowest values for most amino acids.…”
Section: Animal Feedmentioning
confidence: 88%
“…The highest AID and SID for most amino acids were observed for corn-soybean and peanut meals whereas rice bran and corn dried Biogas production (hydrogen) Bálint et al (2005) grains diets presented the lowest values for most amino acids. Although keratinase supplementation contributed to improve amino acids AID and SID for the six diets studied, only in the corn-soybean meal its supplementation significantly improved the crude protein digestibility (Huang et al 2018).…”
Section: Animal Feedmentioning
confidence: 91%